AN ANALYSIS OF TEACHER’S QUESTIONS IN CLASSROOM INTERACTION - Wahyudi Wahyudi (Journal of English Education Program (JEEP), 2019)
This study investigates  the  question  types  employe  by  an  English teacher and the students respond of the questions asked by the teacher in the classroom. To  get  the  data,  the  researchers  administered  questionnaires  and conducted  classroom  observation. The data were obtained by video recording three meetings of English subject, as well as by given questionnaire to the students. The English teacher and her thirty six students were involved as the participants. The types of question were identified using the theory proposed by Brown (2001). The results that the teacher used six out of seven question types; they were: knowledge (33%), comprehension (38%), application (25%), inference, analysis (2%), and synthesis (2%) questions. Furthermore, comprehension questions were highly employed by the English teacher and used to translating, interpreting or extrapolating knowledge of the students. Finally, the writer drew conclusions that the students in MAN Majenang were less active in responding the teacher’s questions. All of students have similar problem, that was they still afraid to express their though and feeling, including to answer the questions given by the teacher.